Numerical simulation of the implant system of a prosthesis and a dental bridge under dynamic loading - Chelahi Chikr, Y.; Bouzouina, K.; Boutabout, B. (Journal of Osseointegration, 2023)
Aim The objective of this study is to analyze the effect of masticatory efforts on the intensity and distribution of the equivalent von Mises stress generated in the bone and in the elements that constitute the tooth structure. Materials and methods Three-dimensional numerical analysis by the element method is concerned with a comparative study between two dental structures subjected to dynamic loads. Each of the dental systems is subjected to a mechanical load simulating the functioning of the tooth in three directions: corono-apical, disto-mesial and linguo-buccal. There are two solutions to replace one or more missing teeth. The first solution is to use three dentures that replace the premolar tooth and the two molar teeth. The second solution is to use a dental bridge system consisting of three crowns that aims to replace the missing first molar tooth by relying on two implants. Results The results show that maximum stresses lead to a risk of deterioration of the cancellous bone first to reach the cortical bone and finally the loosening of the implant. Conclusion A dental bridge may be the best option if the neighboring teeth have large fillings and need crowns in the future. And if the tooth or teeth have been lost for a long time, the gum and bone will be reduced and other procedures are needed instead of the dental implant. However, the downside of the dental bridge system is that it gradually leads to bone loss, because it does not stimulate chewing. In fact, the artificial tooth does not rest on the jawbone, which causes this inconvenience.